Pengaruh Perspektif Pembelajaran dan Pertumbuhan terhadap Kinerja Perspektif Pelanggan pada Pasien Rawat Jalan Instalasi Farmasi Rumah Sakit - Muh Syahruddin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
The aim of this study is to know how the impact of learning-growth perspective and internal business process perspective to performance customer perspective of pharmacy installation for outpatients in BLUD H.M. DjafarHarun Hospital, North Kolaka Region, Southeast Sulawesi. The method of this study is descriptive,non-experimental case study. The data was collected with retrospective and prospective method consist of quantitative and qualitative data. Data was taken from interview with a pharmacist, direct observation, documents survey and questioners to analyze Results of the study are two employees involved in developing training in the year 2012, no training in 2013, based on questioner employee satisfaction was good, work spirit was also good with percentage 83,45%, management information system needs further development. Based on questioner internal business process is good, level of drug stock availability in the year 2012 was 99,12% and in 2013 was 95,14%, dispensing time for powder medicine was 13,65 minutes, dispensing time for ready stock medicine was 3,53 minutes, supplier performance has not been good enough, level of medication error and potential error was low. Based on questioner, customer satisfaction was still low, reliability dimension was 0,02, responsiveness 0,00, tangible 0,00, assurance 0,01, empathy 0,02. 89,36% of patients in 2012 were covered with pharmaceutical service from hospital pharmacy installation,this level decreased in 2013 for 37,20%, the average time for drug information was 25,56 seconds.